ADAPTIVE SOLUTIONS IN AQUACULTURE UNDER THE INFLUENCE OF TRANSFORMATION OF ABIOTIC AND BIOTIC FACTORS - Honcнarova, Olena; Bekh, Vitaliy (European Science, 2023)
The results demonstrate the significant influence of abiotic and biotic factors on the effective parameters in aquaculture. The results reflect the state of study of the issue of European integration of aspects of energy saving into technological maps of